1995
DOI: 10.1002/j.1460-2075.1995.tb07321.x
|View full text |Cite
|
Sign up to set email alerts
|

GCN20, a novel ATP binding cassette protein, and GCN1 reside in a complex that mediates activation of the eIF-2 alpha kinase GCN2 in amino acid-starved cells.

Abstract: GCN2 is a protein kinase that phosphorylates the alpha‐subunit of translation initiation factor 2 (eIF‐2) and thereby stimulates translation of GCN4 mRNA in amino acid‐starved cells. We isolated a null mutation in a previously unidentified gene, GCN20, that suppresses the growth‐inhibitory effect of eIF‐2 alpha hyperphosphorylation catalyzed by mutationally activated forms of GCN2. The deletion of GCN20 in otherwise wild‐type strains impairs derepression of GCN4 translation and reduces the level of eIF‐2 alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
149
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(156 citation statements)
references
References 70 publications
(104 reference statements)
2
149
0
1
Order By: Relevance
“…The uncharged tRNA binds to a regulatory domain in GCN2 that resembles histidyl-tRNA synthetase, and this interaction is believed to induce a conformational change that overcomes an intrinsic defect in the adjacent kinase domain (7)(8)(9)(10). The products of GCN1 and GCN20 are also necessary for the activation of GCN2 by uncharged tRNA in starved cells (11,12). GCN1 and GCN20 form a protein complex (12) that binds to the N-terminal domain (NTD) of GCN2, which is highly conserved among all GCN2 orthologs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The uncharged tRNA binds to a regulatory domain in GCN2 that resembles histidyl-tRNA synthetase, and this interaction is believed to induce a conformational change that overcomes an intrinsic defect in the adjacent kinase domain (7)(8)(9)(10). The products of GCN1 and GCN20 are also necessary for the activation of GCN2 by uncharged tRNA in starved cells (11,12). GCN1 and GCN20 form a protein complex (12) that binds to the N-terminal domain (NTD) of GCN2, which is highly conserved among all GCN2 orthologs.…”
mentioning
confidence: 99%
“…The products of GCN1 and GCN20 are also necessary for the activation of GCN2 by uncharged tRNA in starved cells (11,12). GCN1 and GCN20 form a protein complex (12) that binds to the N-terminal domain (NTD) of GCN2, which is highly conserved among all GCN2 orthologs. The GCN2 NTD is required for kinase function in vivo, and its overexpression impairs complex formation between native GCN1 and GCN2 and produces a dominant Gcn Ϫ (general control noninducible) phenotype (13,14).…”
mentioning
confidence: 99%
“…Evaluation of ABCF2 positives were reported previously (Tsuda et al, 2005a;Nishimura et al, 2007). ATP-binding cassette superfamily F2 protein is a member of ABC transporter superfamily and the GCN20 subfamily (Vasquez de Aldana et al, 1995) and we demonstrated that ABCF2 protein is predominantly located in the cytoplasm of cells (Tsuda et al, 2005a;Nishimura et al, 2007). Thus, in this study, we judged the positivities of this protein based on the cytoplasmic staining into either positive or negative.…”
Section: Immunohistochemistrymentioning
confidence: 82%
“…In ovarian CCC, ABCF2 expression was associated with chemoresistance and OS (Tsuda et al, 2005a, b;Ogawa et al, 2006), while in breast cancer, lack of ABCF2 expression was associated with increased diseasefree survival (Ogawa et al, 2006). ATP-binding cassette superfamily F2 is a member of the GCN20 subfamily of the ABC transporter superfamily (Vasquez de Aldana et al, 1995). Similar to other members of the ABC family, ABCF2 contains a pair of nucleotidebinding domains but it lacks a transmembrane domain (Allikmets et al, 1996;Kerr, 2004), suggesting that it is unlikely to function as a cell membrane transporter, as do other members of the ABC family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation